UK SMEs and business students: An investigation into perceptions of employability for entry-level positions in SMEs - Thomas Shaw (Fields, 2020)
The purpose of this study is to investigate whether Small to Medium-sized Enterprise (SME) and business student perceptions of employability are in alignment. The study considered different variables associated with employability, including the most important candidate employability attribute, the skills required for employment and the skill shortages amongst students. Using qualitative primary research – in the form of face-to-face, semi-structured interviews – the study discovered that personality and experience were more significant than first assumed, due to technological advancements and changes in the working environment. The study revealed that SMEs and students’ perceptions of employability do not align, and that the gap has continued to widen, therefore contributing to under-researched areas of employability literature. A limitation of the study was that it relied on a small number of respondents. The study serves as a benchmark for future research, and the author recommends further research into student and small business employability, as these areas are underdeveloped.